Motivating smokers at outdoor public smoking hotspots to have a quit attempt with a nicotine replacement therapy sample: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Cheung, Yee; Leung, Jessica Pui Kei; Cheung, Chelsia; Li, William; Wang, Man; Lam, Tai
Abstract Background About half of the daily smokers in Hong Kong have never tried and have no intention to quit smoking. More than one-third (37.9 %) of daily smokers have attempted to quit but failed. Nicotine replacement therapy (NRT) is a safe and effective pharmacotherapy to increase abstinence by reducing withdrawal symptoms during the early stage of smoking abstinence. However, the prevalence of NRT use in Hong Kong is lower than in most developed countries. The proposed study aims to assess the effectiveness of providing free NRT samples to smokers on increasing quit attempts and the quit rate. Methods Trained university undergraduate students as ambassadors will invite smokers at outdoor public smoking hotspots to participate in the randomized controlled trial, in which eligible smokers will be randomized to receive a 1-week free NRT sample and medication counselling (intervention) or advice to purchase NRT on their own (control). The primary outcome is self-reported quit attempts (no smoking for at least 24 hours) in the past 30 days at 1-month and 3-month telephone follow-up. Discussion The findings will inform the effectiveness of delivering free NRT samples at outdoor public smoking hotspots to increase quit attempts and abstinence. The study will also provide information on smokers' adherence to the NRT sample, side effects and safety issues related to the usage. This will improve the design of a large trial to test the effect of the NRT sample. Trial registration ClinicalTrials.govNCT02491086 . Registered on 7 July 2015.